Stem rust resistance in wheat is suppressed by a subunit of the mediator complex - Hiebert, Colin W; Moscou, Matthew J; Hewitt, Tim; Steuernagel, Burkhard; Hernández-Pinzón, Inma; Green, Phon; Pujol, Vincent; Zhang, Peng; Rouse, Matthew N; Jin, Yue; McIntosh, Robert A; Upadhyaya, Narayana; et al. (Nature communications, 2020)
Stem rust is an important disease of wheat that can be controlled using resistance genes. The gene SuSr-D1 identified in cultivar 'Canthatch' suppresses stem rust resistance. SuSr-D1 mutants are resistant to several races of stem rust that are virulent on wild-type plants. Here we identify SuSr-D1 by sequencing flow-sorted chromosomes, mutagenesis, and map-based cloning. The gene encodes Med15, a subunit of the Mediator Complex, a conserved protein complex in eukaryotes that regulates expression of protein-coding genes. Nonsense mutations in Med15b.D result in expression of stem rust resistance. Time-course RNAseq analysis show a significant reduction or complete loss of differential gene expression at 24 h post inoculation in med15b.D mutants, suggesting that transcriptional reprogramming at this time point is not required for immunity to stem rust. Suppression is a common phenomenon and this study provides novel insight into suppression of rust resistance in wheat.
Keywords: mutace; Triticum; nemoci rostlin; Phenotype; Plant Immunity; mapování chromozomů; Chromosome Mapping; odolnost vůči nemocem; Disease Resistance; Chromosomes, Plant; chromozomy rostlin; Mutation; Genes, Plant; Poaceae; rostlinné geny; imunita rostlin; Mediator Complex; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; lipnicovité; duplikace genu; Plant Diseases; exprese genu; fenotyp; mediátorový komplex; pšenice; Basidiomycota; Gene Duplication; Gene Expression